DIETARY HABITS AND HEALTH-RELATED BEHAVIORS AMONG MEDICAL DENTISTRY STUDENTS - A CROSS-SECTIONAL STUDY - Iorga Magdalena; POP Lavinia; MURARU Iulia-Diana; ALWAN Sinan; IOAN Beatrice-Gabriela (Romanian Society of Oral Rehabilitation, 2018)
The aim of the study is to identify dietary habits and other health-related behaviors among dentistry students enrolled in first year of study in a medical university. Material and methods: a number of 81 students (74.1% female) aged M = 19.29 ± 0.84, ranged 18-23 years old were included in the research. The majority of the students reside in urban areas (77.8%, N = 63). Socio-demographic, medical, dietary and health-related data were registered. Statistical analysis was done using SPSS v.20. Results: 21% of students usually walk to reach their school. They usually sleep 6.34 ± 1.39 hours. 55.5% of students go to sleep between 12 pm and 1 am. 33.33% reported that they used diets in order to reduce their BMI. More than half of students (58%) denied smoking and ¼ denied drinking alcohol. 66.7% of students had a normal BMI. More than 85.2% don't have regular meals. A positive correlation was found between egg consumption and water intake (r=.304, p=.006) and number of fruits eaten per day (r=.304, p=.006). More concretely, the more students eat eggs, the more they drink water and eat fruits. Also, there is a negative correlation between the number of fruits students eat per day and number of fast-food meals per week (r=-.249, p=.025). In other words, the more fruits students consume, the less fast-food they eat. Conclusion: It is important for dentistry students to make themselves aware about effective dietary habits during their academic years in order to adjust their nutritional behavior and improve their quality of life.